2015
DOI: 10.1002/tea.21215
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between student success in introductory university chemistry and approaches to learning outside of the classroom

Abstract: The study reported here examines the learning approaches adopted by students enrolled in introductory chemistry at a public university. To evaluate learning approaches, a group of 61 students enrolled in the course were interviewed at three time-points during the semester, specifically to ascertain how they prepared for the exams. From these interviews, the Learning Approaches Framework for Chemistry was developed. The framework describes four levels of learning approaches that were determined based on the act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 31 publications
1
28
0
Order By: Relevance
“…It is generally accepted that there are two main approaches to learning, that is, surface approaches such as rote learning, and deep approaches such as meaningful learning. These approaches have been found in engineering problem solving (Sinapuelas & Stacy, 2015), in solving applied problems (Martyn et al, 2014), and in learning in the context of online discussions . The results indicate that surface approaches tend to be oriented toward engagement in the learning environment which promotes reproduction.…”
Section: Contribution Of This Paper To the Literaturementioning
confidence: 99%
“…It is generally accepted that there are two main approaches to learning, that is, surface approaches such as rote learning, and deep approaches such as meaningful learning. These approaches have been found in engineering problem solving (Sinapuelas & Stacy, 2015), in solving applied problems (Martyn et al, 2014), and in learning in the context of online discussions . The results indicate that surface approaches tend to be oriented toward engagement in the learning environment which promotes reproduction.…”
Section: Contribution Of This Paper To the Literaturementioning
confidence: 99%
“…Both tutors and tutees tended to rely predominantly on more superficial learning strategies (taking notes and highlighting important information). We had expected to find evidence that tutors, who had excelled academically in the nursing program, would prefer "deeper" learning strategies as they promote learning and academic success, [16,19,20] but we found no significant differences in preferred learning/studying strategies. However, in the Tutee-Focused Tutoring Program Evaluation Survey, tutees identified that tutors clarified concepts of course materials, helped them discover new ways of learning course materials, and explained information in a way they could understand-behaviors that are more reflective of deeper metacognitive strategies.…”
Section: Discussionmentioning
confidence: 61%
“…More importantly, the positive results of PEB observed in this study were largely because of an effectively designed education-based strategy. Theoretical understanding limits a behaviour because not all theories can be translated into action (Sinapuelas and Stacy, 2015). The focus group interviews’ data indicated that participants were pleased with the types of information provided, the breadth of information made available to them and the personal connection between nature and participants.…”
Section: Discussionmentioning
confidence: 99%